The inflation rate disconnect puzzle: On the international component of trend inflation and the flattening of the Phillips curve - Guido Ascari; Luca Fosso (Norges Bank, 2021)
Since 2000 U.S. inflation has remained both below target and silent to domestic slack and monetary interventions. A trend-cycle BVAR decomposition explores the role of imported intermediate goods in explaining the puzzling behaviour of inflation. The trend analysis shows that, starting from the '90s, despite very well-anchored expectations, slow-moving imported "cost-push" factors induced deflationary pressure keeping trend inflation below target. The cycle block provides evidence in favour of a flattening of the Phillips curve, mainly attributable to a weaker wage pass-through. The business cycle behaviour of inflation is determined by a shock originating abroad, which indeed generates the main bulk of volatility in the international prices of intermediate goods and is poorly connected to the domestic slack.
hdl:11250/2835494
Keywords: C11; C32; E3; E31; E52; 330; Trend-Cycle Decomposition; Trend Inflation; Global Inflation; Phillips Curve